God and government : twenty-five years of fighting for equality, secularism, and freedom of conscience - Lynn, Barry W. (Prometheus Books, 2015)
"A central player in every major church-state-separation battle for decades, the Rev. Barry W. Lynn understands the complexities of this divisive issue like few others. As a long-time activist, a civil rights lawyer, and an ordained minister in the United Church of Christ, he offers a unique perspective and a wealth of experience on church-state controversies. In this lively book, he has compiled his writings from various sources to explore in depth the many ways religious extremists have attempted to erode individual liberties. The topics range from publicly-promoted prayer to efforts to undermine public education and replace it with taxpayer-subsidized vouchers for religious schools, interfering with end-of-life and reproductive rights, censorship, and belligerence directed against nonbelievers and minorities. Lynn concludes that the ultimate goal of these extremist forces--consisting mainly of the Protestant Religious Right and the Roman Catholic hierarchy--is the creation of a corporate theocracy, a decidedly undemocratic system of government in which nonconservative Christians, along with humanist, feminists, and the LGBTQ community, are relegated to second-class status in America"--